Nascendo pais: a transição para a parentalidade em reprodução assistida (RA) - Bernauer, Maura Castello (2009)
In this study, is searched to reflect concerning the impacts of the infertility in the subjectivity of men and women that had submitted and had children through ART; and about the process of conjugality transition to parenthood after the birth of the son. From the approach of the theoretical boarding of Sociohistoric Psychological of Vygotsky, it was explored symbolic conception of genre to implement a perspective denaturalizing of maternity and of the paternity where the concept of the identities was evaluated of masculine and feminine genre that they had been if modifying throughout the years, through social behaviors on sexuality and reproduction. And in which one searched to apprehend meanings and felingst through open interview in depth, with three couples infertile heterosexuals whom had submitted treatment of ART and has a first son (s) already born at least for one year in a private clinic, in a city near the city of São Paulo. Thus being: Couple 1 Ana (35, degree in Adm) and Bruno (38, graduated in law); they are married for 6 years and have a couple of twin children of 2 years of age. Couple 2 - Carla (39, degree in Adm) and Daniel (44, high school degree, works with commerce); they are married for 13 years and have a son of 2 and a half years. Couple 3 - Elsa (36, degree in Computer Science) and Fábio (34, degree in Computer Science); they are married for 7 years and have a son of 2 years. Readings of the collected date had been made that they had allowed a process of aglutination of 66 pré-indicators, for the similarity, complementary or contraposition. After this process had gotten a lesser diversity of subjects, being able itself to agglutinate in 29 indicators. To leave of the reverse speed-reading of the material, the joint process was made that resulted in the organization of meaning core: (1) treatment of ART, pregnancy and childbirth; (2) conjugality; (3) spirituality; (4) family relationships and (5) parenthood. To leave of the partner-historical context of the conjugal and parental bows, we understand the existing relations between conjugality e parentahood of men and women who had had son (s) through ART. The treatment of ART produces the construction of personal directions and redimension the meanings of the transistion for parenthood. The studied couples continue in the condition of infertile although they have children. The representation of the biological bond (implied: to conceive, pregnancy and childbirth) for confirmation of the sort identities is the main reason that leads the couples to the ART services taking them, to neglect the adoption or to remain without children. The idea of nature in its ideological function it strengthens the moral order and it generates culpability. It can be hypothesing that emotional problems are decurrent of not development of parenthood, that is of the relation of the children with the adults, because many men and women did not desire to have children, they only wanted to be father and mother, to confirm its femininity and manhood. We conclude that denaturalizing the meanings of feminine/maternity e masculine/paternity they had extended our perspectives of the understanding of the relations of sort and its repercussions on the subjectivity in the contemporaneousness